2018
DOI: 10.1007/s10508-018-1211-x
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Social Institutions and Preventive Healthcare Seeking for Black Men Who Have Sex with Men: The Promise of Biomedical HIV Prevention

Abstract: Research on gender and health, including research conducted among Black men who have sex with men (BMSM), has primarily focused on how gender norms and roles shape healthcare engagement. Here we advance that work by demonstrating how a broader theorization of gender, particularly one that moves beyond gender norms and performance to incorporate structures such as the healthcare system and the labor market, can facilitate an understanding of how gender affects preventive healthcare seeking among BMSM, particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 66 publications
(90 reference statements)
1
20
0
Order By: Relevance
“…17 Patients who might be interested in PrEP report feeling that interactions with providers are ''scripted'' in ways that do not allow full disclosure of sexual behavior or concerns. 18 Men of color are particularly likely to report that providers make false assumptions about their heterosexuality, or relate that fears of ''transgressing'' masculine norms in health care settings limit their access to preventive care. 18 However, even if PrEP assessment tools were widely disseminated and providers were taught how to administer them effectively, data suggest that there would still be a fundamental problem with this strategy for identifying appropriate PrEP candidates stemming from a disconnect in data about HIV transmission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Patients who might be interested in PrEP report feeling that interactions with providers are ''scripted'' in ways that do not allow full disclosure of sexual behavior or concerns. 18 Men of color are particularly likely to report that providers make false assumptions about their heterosexuality, or relate that fears of ''transgressing'' masculine norms in health care settings limit their access to preventive care. 18 However, even if PrEP assessment tools were widely disseminated and providers were taught how to administer them effectively, data suggest that there would still be a fundamental problem with this strategy for identifying appropriate PrEP candidates stemming from a disconnect in data about HIV transmission.…”
Section: Resultsmentioning
confidence: 99%
“…18 Men of color are particularly likely to report that providers make false assumptions about their heterosexuality, or relate that fears of ''transgressing'' masculine norms in health care settings limit their access to preventive care. 18 However, even if PrEP assessment tools were widely disseminated and providers were taught how to administer them effectively, data suggest that there would still be a fundamental problem with this strategy for identifying appropriate PrEP candidates stemming from a disconnect in data about HIV transmission. For a given individual patient, there is no denying that as the number of risk factors (e.g., number of partners, number of sex acts) increases, their risk for HIV exposure increases as well.…”
Section: Resultsmentioning
confidence: 99%
“…The microsystem level represents where individuals participate directly with their surroundings and should therefore include the following three key elements. Firstly, information should be provided on how to access PrEP to address current structural barriers and challenges, [ 52 , 57 , 68 , 70 , 73 , 85 , 94 , 97 , 101 , 108 , 114 117 ] such as cost, [ 113 , 118 , 119 ] geography, [ 83 ] and stigma [ 78 , 82 , 120 ]. Secondly, general education about PrEP should be made accessible across a range of media, to a broad geographic and culturally diverse audience.…”
Section: Resultsmentioning
confidence: 99%
“…A surprising finding was the lack of open discussion that was experienced during consultations. From the perspective of the service user, conversations around sexual behaviour were missed as they were seen to be difficult, [62,67,80] uncomfortable, [61,97] or as a consequence of the service providers' failure to take complete histories [56,60,68,78,79,86,96]. Some studies reported the lack of disclosure of sexual activity [80,82,99] and PrEP use [80,82,99], due to concerns for privacy and confidentiality, perceived stigma, fear of negative repercussions and embarrassment.…”
Section: Theme Two: Prep Prescriber Experiences Therapeutic Alliancementioning
confidence: 99%
See 1 more Smart Citation